When Vigilantism Becomes Social Justice: Legal Intervention in Community-Based Punishment in Indonesia - Andi Bangun Sanjaya (JUSTISIA GLOBAL EDUKASI, 2026)
Vigilante punishment remains a recurring social phenomenon in Indonesia, particularly when communities perceive formal law enforcement as slow, ineffective, or disconnected from local notions of justice. Practices such as collective beating, public humiliation, forced confession, and informal punishment are often justified as necessary forms of community protection. This article examines how legal intervention should respond to community-based punishment without disregarding the social conditions that encourage vigilantism. Using a socio-legal approach, the study analyzes the interaction between formal criminal law, community norms, perceptions of justice, and informal mechanisms of social control. The analysis demonstrates that vigilantism cannot be understood solely as an individual violation of criminal law; it also reflects institutional distrust and the community's demand for immediate justice. The article argues that punitive legal intervention alone may be insufficient and can further distance communities from formal legal institutions. Its contribution lies in proposing a community-responsive model of legal intervention that combines law enforcement, restorative mechanisms, public legal education, and institutional accountability. Such an approach may strengthen access to justice while preventing community-based punishment from becoming an alternative form of unlawful social justice.